Lysozyme functionalized zinc-oxide nanoparticles: Synthesis, characterization, and antibacterial assessment against Staphylococcus aureus with futuristic application in wastewater monitoring - Suneeti Singh; Pavni Rekhi; Jewel Mary Saju (Next Nanotechnology, 2025)
Access to clean drinking water remains a global concern, primarily due to the presence of biological, inorganic, and organic pollutants. Among the biological contaminants, waterborne pathogens pose a significant threat to human well-being. Since nanoparticle-based biosensors have a higher sensitivity for detecting bacteria than conventional detection techniques, they have become increasingly prevalent. In this context, the current study reports zinc oxide nanoparticles functionalized with lysozyme (ZnO@LY NPs) via a modified oxidation-reduction mechanism, followed by an assessment of their antibacterial activity. The morphology and size of the functionalized ZnO@LY NPs were determined using Transmission electron microscopy-energy dispersive X-ray spectroscopy (TEM-EDX), X-ray diffraction (XRD), dynamic light Scattering (DLS), and zeta potential analysis, which revealed nanoparticles of size between 14 and 32 nm with + 31.1 mV charge. Further, the functionalization of ZnO with lysozyme was confirmed using Fourier-transform infrared spectroscopy (FTIR) and Ultraviolet-Visible (UV-Vis) spectroscopy. The antibacterial efficacy of ZnO@LY NPs and ZnO NPs against Gram-positive bacteria (Staphylococcus aureus) was assessed in a comparative study. After 30 min and 24 h of treatment with ZnO@LY NPs at 250 ppm, the agar spot assay revealed the absence of colonies. Similarly, ZnO@LY NPs exhibited a 25 % stronger and statistically significant antibacterial impact than non-functionalized ZnO NPs in the bacterial growth inhibition assay, as confirmed by repeated measures (RM)-ANOVA analysis. Moreover, Dunnett's multiple comparison test revealed that ZnO@LY NPs showed a dose-dependent linear response when compared to ZnO NPs. The superior antibacterial performance of ZnO@LY NPs is attributed to improved bacterial surface interactions, stability, and biocompatibility facilitated by lysozyme functionalization. These findings suggest a potential application of ZnO@LY nanoparticles in biosensors for on-site pathogen detection in wastewater.